Surface Routing for Wireless Power Transfer Using 2-D Relay Resonator Arrays - Masahiro Morita; Takuya Sasatani; Ryo Takahashi; Yoshihiro Kawahara (IEEE Access, 2021)
Wireless power transfer via magnetic resonance coupling offers the prospect of autonomously charging connected devices. Previous work demonstrated that the system deployment can be facilitated by “routing” power on 2-D relay resonator arrays, using the multi-hop phenomenon. Power propagates through untethered relay resonators in such systems, and the routing strategy significantly affects the power transfer efficiency. However, most previous studies limit the routing to line-shaped routes, which compromises power transfer efficiency to preserve the simplicity of analysis. Here we show a surface routing approach, which can be orderly generated and is more efficient than linear routing. The confronting challenge is the complex representation of cross-coupled relays, which this work overcomes by conditioning the resonators’ current by appending additional loading conditions to the relays. Simulation-based evaluations show that the proposed approach improves the efficiency by up to 10% in 1.5 m range power delivery.